(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Construction manager faces numbers of challenges, through which some are new to the construction industry and some are many years old. The construction problems like workforce consideration, safety, time constraints, and altering nature of work. To minimize such issues proper project management tool must be taken in account. To achieve the project success effective cost and time management should be taken in account while planning the entire project. This paper is focussing on Bridge-Project scheduled by Oracle’s Primavera P6 software.